Shape Casting 6th International Symposium - Tiryakioǧlu, Murat; Jolly, Mark; Byczynski, Glenn (The Minerals, Metals & Materials Series, 2016)
This collection presents papers on the science, engineering, and technology of shape castings, with contributions from researchers worldwide. Among the topics that are addressed are structure-property-performance relationships, modeling of casting processes, and the effect of casting defects on the mechanical properties of cast alloys.